Analysis of AGE modified proteins and RAGE expression in HER2/neu negative invasive ductal carcinoma - Korwar, Arvind M.; Bhonsle, Hemangi S.; Chougale, Ashok D.; Kote, Sachin S.; Gawai, Kachru R.; Ghole, Vikram S.; Koppikar, Chaitanyananda B.; Kulkarni, Mahesh J. (Biochemical and Biophysical Research Communications, 2012)
Cancer is associated with increased glycolysis and carbonyl stress. In view of this, AGE modified proteins were identified from clinical breast cancer tissue using 2DE-immunoblot and mass-spectrometry. These proteins were identified to be serotransferrin, fibrinogen gamma chain, glycerol-3-phosphate dehydrogenase, lactate dehydrogenase, annexin II, prohibitin and peroxiredoxin 6, which have established role in cancer. Further, RAGE expression and its downstream signaling proteins NADPH oxidase and NF-kB were studied. Role of these AGE modified proteins and RAGE signaling in breast cancer is discussed. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: advanced glycation end products; Breast cancer; RAGE

Proteomic profiling and interactome analysis of ER-positive/HER2/neu negative invasive ductal carcinoma of the breast: towards proteomics biomarkers - Korwar, Arvind M.; Bhonsle, Hemangi S.; Ghole, Vikram S.; Gawai, Kachru R.; Koppikar, Chaitanyananda B.; Kulkarni, Mahesh J. (OMICS-A Journal of Integrative Biology, 2013)
Breast cancer, especially ER positive/HER2/neu negative IDC, is the predominant subtype of invasive ductal carcinoma. Although proteomic approaches have been used towards biomarker discovery in clinical breast cancer, ER positive/HER2/neu negative IDC is the least studied subtype. To discover biomarkers, as well as to understand the molecular events associated with disease progression of estrogen receptor positive/HER2/neu negative subtype of invasive ductal carcinoma, differential protein expression profiling was performed by using LC-MSE (MS at elevated energy). A total of 118 proteins were identified, of which 26 were differentially expressed. These identified proteins were functionally classified and their interactions and coexpression were analyzed by using bioinformatic tools PANTHER (Protein Analysis THrough Evolutionary Relationships) and STRING (Search Tool for the Retrieval of Interacting Genes). These proteins were found to be upregulated and were involved in cytoskeletal organization, calcium binding, and stress response. Interactions of annexin A5, actin, S100 A10, glyceraldehyde 3 phosphate dehydrogenase, superoxide dismutase 1, apolipoprotein, fibrinogen, and heat shock proteins were prominent. Differential expression of these proteins was validated by two-dimensional gel electrophoresis and Western blot analysis. The cluster of these proteins may serve as a signature profile for estrogen receptor positive/ HER2/neu negative subtype.

Synergistic action of flavin containing NADH dependant azoreductase and cytochrome P450 monooxygenase in azoaromatic mineralization - Oturkar, Chetan C.; Othman, Munif A.; Kulkarni, Mahesh J.; Madamwar, Datta; Gawai, Kachru R. (RSC Advances, 2013)
An alkaliphilic strain Bacillus lentus Bl377 was isolated from contaminated soil of the textile area of Solapur, India. The strain was able to degrade almost 98% of recalcitrant azoic compounds by a mutually regulated process of azoreductase and a monooxygenase system. An enzyme activity study and a periodical carbon monoxide (CO) binding spectra study on a UV-visible spectrophotometer revealed that the intermediate amines formed by typical azoreduction (N=N cleavage), subsequently underwent hydroxylation by the cytochrome P450 monooxygenase (CYP450) system. Azoreductase was purified by chromatographic techniques and characterization by MALDI-TOF substantiated its identity as FMN containing NADH dependent azoreductase of 32 kDa in size. Surprisingly, purified azoreductase showed the highest activity at 80 degrees C and pH 8.0. An increase in the activity of superoxide dismutase after decolorization confirmed the signature of oxidative stress and its involvement in the dismutation of reactive metabolites. Intermediate metabolite analysis by HPLC, GC-MS and FTIR and the removal of total organic carbon (TOC) suggested the azoaromatics' degradation leads to mineralization via a TCA cycle.